The influence of relational factors on successful succession in family businesses: A comparative study of owner-managers and successors - E. Venter; C. Boshoff; G. Maas (South African Journal of Business Management, 2003)
Family businesses are fast becoming the dominant form of business enterprise in both developing and developed economies and play a vital economic and social role in these economies. As family businesses are a primary contributor to the economic and social well-being of all capitalist societies, their general lack of longevity is a cause for concern. One of the main reasons (if not the single most important reason) of the high failure rate among first- and second-generation family businesses is their inability to manage the complex process of ownership and management succession from one generation to the next. Hence, the primary objective of this study is to identify the relational or human factors that impact on successful succession. The results indicate that the willingness of the successor to take over the family business, the owner-manager's trust in the successor's abilities and intentions to manage the business, and the owner-manager's interest outside the business are important to the success of succession for both owner-managers and successors. Furthermore, the more the successor perceives harmony within the family, the more satisfied the successor will be with the succession process.
Keywords: 650